High-dose-rate interstitial brachytherapy for female peri-urethral cancer - Sharma, Daya Nand; Gandhi, Ajeet Kumar; Bhatla, Neerja; Kumar, Sunesh; Rath, Goura Kisor (Journal of Contemporary Brachytherapy, 2016)
Purpose: Peri-urethral cancer (PUC) in females is a rare malignancy. Surgery is not usually contemplated due to associated morbidity. Radiation therapy (RT) can be employed in the form of interstitial brachytherapy (IBT) alone for early lesions, and external beam radiation therapy (EBRT) with or without IBT for advanced lesions. We report our first experience in the literature to evaluate the role of high-dose-rate (HDR) IBT in female PUC. Material and methods : Between 2008 and 2013, 10 female patients with PUC (5 primary and 5 recurrent) were treated with HDR-IBT with or without EBRT at our center. Size of the lesion ranged from 1.5 cm to 5.0 cm. A 2-3 plane free-hand implant was performed using plastic catheters. The prescribed dose of HDR-IBT was 42 Gy in 14 fractions for brachytherapy alone (5 patients), and 18-21 Gy for the boost along with EBRT (5 patients). Patients were followed up regularly for assessment of disease control and toxicity. Results: At a median follow up of 25 months, six patients were disease free at their last follow up. Four patients developed recurrence: 2 at inguinal nodes, 1 at local site, and 1 at both local as well as inguinal nodes. Moist desquamation was the commonest acute toxicity observed in all 5 patients treated with IBT alone, which healed within 4 weeks’ time. Overall, grade II delayed complication rate was 30%. Conclusions : Though small sample size, the results of our study have shown that HDR-IBT provides good loco-regional control with acceptable toxicity for female PUC.